The Implementation of Ethical Concepts Toward Waste in the Design of Farms and the Cultivation of Ducks in Mojokerto - Al Manuddin, A.H.; Mutiara, Elok; Gautama, Achmad Gat (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2019)
Location of the design object located in Mojosari Mojokerto Regency, the selection of this location is based on many ducks and the area has a type of duck that has been known in Indonesia namely the duck Mojosari. In this area, there are problems with the environment caused by the pollution of livestock waste in the region, especially the pollution of rivers that cross the area. Through the application of the ethical concept of waste on livestock planning and processing, duck is a container and a solution to develop the potential of ducks and provide solutions to the environmental problems that cause it. Application. The ethical concept of waste on this design object, as a solution for the development and handling of the problems in this region. The ethical concept of waste is implemented by adjusting the design needs with the environmental problems posed so that the design object optimizes livestock waste potential and environmental potential. Adjustment of needs and problems in this environment is intended as an ethical in object design.